The impact of adolescent physical activity on quality of life: a moderated mediation model - Ma, Sen; Gao, Yan; Zhao, Liangyu; Sui, Wenze; Yang, Yuke; Hu, Yining (Frontiers in Public Health, 2025)
BackgroundQuality of Life (QoL) is a crucial multi-dimensional structure in the development process of adolescents. As a key topic in adolescent research, existing achievements all indicate that participating in physical activities can improve the QoL of adolescents. However, the underlying mechanisms—the mediating role of anxiety and the underlying gender differences—remain insufficiently understood.PurposeThis study investigates the mechanisms by which adolescent physical activity influences QoL. Specifically, it examines the mediating role of anxiety and explores gender as a moderating factor. A multidimensional analysis of QoL outcomes is also conducted to provide a more nuanced understanding.MethodsWe analyzed cross-sectional data from 9,504 adolescents across 17 cities in Shandong Province, China. The collected data were statistically analyzed using SPSS 27.0. Build a moderated mediation model using the PROCESS macro of SPSS.Results(1) There is a significant positive correlation between teenagers’ participation in sports and their QoL (β = 4.243, p < 0.01). (2) Anxiety plays a key mediating role between teenagers’ participation in sports and their QoL (β = 0.594, p < 0.05). (3) Gender plays a significant positive moderating role between adolescent sports participation and QoL (β = 0.781, p < 0.01). (4) Gender plays a significant positive moderating role between anxiety and QoL (β = 1.214, p < 0.05). (5) Gender plays a significant positive moderating role in the relationships between anxiety and living environment (β = 0.536, p < 0.01).ConclusionTeenagers’ participation in sports can directly or indirectly improve their QoL by reducing anxiety. Meanwhile, gender plays a moderating role in it. Furthermore, gender plays a significant moderating role in the relationships between anxiety and psychosocial function, anxiety and physical and mental health, anxiety and living environment, and exercise participation and physical and mental health. These findings emphasize the importance of adopting gender-specific strategies in physical intervention measures to improve the QoL of adolescents.